Perceptions, satisfactions, and performance of undergraduate students during Covid-19 emergency remote teaching - Wilhelm, Jessica; Mattingly, Spencer; Gonzalez, Victor H (Anatomical sciences education, 2022)
Due to the Covid-19 pandemic, the education system worldwide faced sudden and unforeseen challenges. Many academic institutions closed their doors, forcing both educators and students to transition to Emergency Remote Teaching (ERT) for the remainder of the semester. This transition eliminated hands-on experiences, increased workload, and altered curricula. However, these aspects, as well as students' perceptions, study habits, and performance in response to ERT remain poorly documented. This contribution describes changes in the curriculum of an undergraduate cadaver-based laboratory, and explores students' performance, self-perceived learning, and overall satisfaction during this educational crisis. Online content delivery for this course included both asynchronous instruction and synchronous discussion sessions. While formative assessments remained the same, online spotter examinations included short answer, multiple choice, multiple answer, ordering, and true and false questions. Despite examination grades improving 20% during ERT, students reported lower levels of learning, confidence, and engagement with the course materials when compared to the face-to-face portion of the class. The most prevalent challenges identified by students were those related to the loss of access to cadaver-based learning, including difficulty identifying and visualizing structures in three dimensions, and the loss of context and sensorial cues. Flexibility in taking examinations and learning the material at their own pace were recognized as positive outcomes of the ERT transition. While the resulting student perceptions and performances are unsurprising, they offer insight into the challenges of fostering a productive learning environment in a future threatened by epidemic outbreak and economic uncertainty.